(t-4)(4)+(t-1)(4)=(5)(t-1)(t-4)

Simple and best practice solution for (t-4)(4)+(t-1)(4)=(5)(t-1)(t-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (t-4)(4)+(t-1)(4)=(5)(t-1)(t-4) equation:


Simplifying
(t + -4)(4) + (t + -1)(4) = (5)(t + -1)(t + -4)

Reorder the terms:
(-4 + t)(4) + (t + -1)(4) = (5)(t + -1)(t + -4)

Reorder the terms for easier multiplication:
4(-4 + t) + (t + -1)(4) = (5)(t + -1)(t + -4)
(-4 * 4 + t * 4) + (t + -1)(4) = (5)(t + -1)(t + -4)
(-16 + 4t) + (t + -1)(4) = (5)(t + -1)(t + -4)

Reorder the terms:
-16 + 4t + (-1 + t)(4) = (5)(t + -1)(t + -4)

Reorder the terms for easier multiplication:
-16 + 4t + 4(-1 + t) = (5)(t + -1)(t + -4)
-16 + 4t + (-1 * 4 + t * 4) = (5)(t + -1)(t + -4)
-16 + 4t + (-4 + 4t) = (5)(t + -1)(t + -4)

Reorder the terms:
-16 + -4 + 4t + 4t = (5)(t + -1)(t + -4)

Combine like terms: -16 + -4 = -20
-20 + 4t + 4t = (5)(t + -1)(t + -4)

Combine like terms: 4t + 4t = 8t
-20 + 8t = (5)(t + -1)(t + -4)

Reorder the terms:
-20 + 8t = 5(-1 + t)(t + -4)

Reorder the terms:
-20 + 8t = 5(-1 + t)(-4 + t)

Multiply (-1 + t) * (-4 + t)
-20 + 8t = 5(-1(-4 + t) + t(-4 + t))
-20 + 8t = 5((-4 * -1 + t * -1) + t(-4 + t))
-20 + 8t = 5((4 + -1t) + t(-4 + t))
-20 + 8t = 5(4 + -1t + (-4 * t + t * t))
-20 + 8t = 5(4 + -1t + (-4t + t2))

Combine like terms: -1t + -4t = -5t
-20 + 8t = 5(4 + -5t + t2)
-20 + 8t = (4 * 5 + -5t * 5 + t2 * 5)
-20 + 8t = (20 + -25t + 5t2)

Solving
-20 + 8t = 20 + -25t + 5t2

Solving for variable 't'.

Reorder the terms:
-20 + -20 + 8t + 25t + -5t2 = 20 + -25t + 5t2 + -20 + 25t + -5t2

Combine like terms: -20 + -20 = -40
-40 + 8t + 25t + -5t2 = 20 + -25t + 5t2 + -20 + 25t + -5t2

Combine like terms: 8t + 25t = 33t
-40 + 33t + -5t2 = 20 + -25t + 5t2 + -20 + 25t + -5t2

Reorder the terms:
-40 + 33t + -5t2 = 20 + -20 + -25t + 25t + 5t2 + -5t2

Combine like terms: 20 + -20 = 0
-40 + 33t + -5t2 = 0 + -25t + 25t + 5t2 + -5t2
-40 + 33t + -5t2 = -25t + 25t + 5t2 + -5t2

Combine like terms: -25t + 25t = 0
-40 + 33t + -5t2 = 0 + 5t2 + -5t2
-40 + 33t + -5t2 = 5t2 + -5t2

Combine like terms: 5t2 + -5t2 = 0
-40 + 33t + -5t2 = 0

Factor a trinomial.
(-5 + t)(8 + -5t) = 0

Subproblem 1

Set the factor '(-5 + t)' equal to zero and attempt to solve: Simplifying -5 + t = 0 Solving -5 + t = 0 Move all terms containing t to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + t = 0 + 5 Combine like terms: -5 + 5 = 0 0 + t = 0 + 5 t = 0 + 5 Combine like terms: 0 + 5 = 5 t = 5 Simplifying t = 5

Subproblem 2

Set the factor '(8 + -5t)' equal to zero and attempt to solve: Simplifying 8 + -5t = 0 Solving 8 + -5t = 0 Move all terms containing t to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -5t = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -5t = 0 + -8 -5t = 0 + -8 Combine like terms: 0 + -8 = -8 -5t = -8 Divide each side by '-5'. t = 1.6 Simplifying t = 1.6

Solution

t = {5, 1.6}

See similar equations:

| sinx=(x^2)/(625pi^2) | | 7=2b-8+1 | | 7.6x-3.4=11.8 | | -5(3n+3)=10 | | (T-9)(T+64)=0 | | 7.5x-1.6=13.4 | | (t+4)(4)+(t+4)(4)=(t-4)(t+4)(5) | | 6.6x-1.3=11.9 | | 4(3z+1)-5(z+8)=3(z+1) | | 1/t-4 | | 21=6-3a-3 | | 8k-4k=0 | | 2+9(x-3)=1-9(x-8) | | 5t*t-8t+112=0 | | n-6-4=-16 | | 6x+24=126 | | -4r-4r=-8 | | 12xy= | | -11-8y=0 | | (4a/b^2)(3/2a^2b^2) | | x+3-3=-1 | | 3n-2n=8 | | 6xy+3x^2y= | | 11.6/2 | | 11/15=3/5p-1/5p | | X^4-9x+14=0 | | 5x+7+x=91 | | Inx+Inx^4=5 | | Inx+Inx^4= | | 16x+20y=0 | | (x-y)(3x+y)= | | 7/2y-13=-6 |

Equations solver categories